O Mercosul aos vinte anos: Uma avaliaç\~ao econômica - Renato Baumann (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– On March, 2011 the signing of the Treaty of Assunción by Argentina, Brazil, Paraguay and Uruguay celebrated its 20th anniversary. Preferential trade agreements that create joint economic spaces might be seen as useful tools to promote economic development. This article discusses to what extent this can be said from Mercosur. It is shown that - as different from what is seen in other regions - there has no been no major achievement insofar as the economic distance between the participating countries is concerned.
Keywords: F14; F43; F50; O54; P50; 330; Regionale Wirtschaftsintegration; Erwerbstätigkeit; Wirtschaftswachstum; Mercosur-Staaten